Relationship between Iron deposition and T lymphocytes in children with β-thalassemia with haematopoietic stem cell transplantation - Zhou, Yuhang; Luo, Jianming (Frontiers in Pediatrics, 2022)
Background β-Thalassemia cellular immunity is associated with iron overload. However, the relationship between varying degrees of iron deposition and T cell immune recovery after allogeneic haematopoietic stem cell transplantation(allo-HSCT) in children remain unclear. Methods A retrospective analysis was performed on 84 children with β-Thalassemia undergoing sibling allo-HSCT. According to the degrees of hepatic iron deposition, patients were divided into four classes. T lymphocyte counts were measured. Hepatic iron deposition was assessed by T2* MRI. Epstein–Barr virus and cytomegalovirus infection rates and graft-vs.-host disease incidence were recorded. Results Immune recovery after allo-HSCT was compared between the two groups. Normal vs. mild group: CD4 cells were higher at 1, 3, and 6 months (P < 0.05), CD3 and CD8 cells were higher at 3 and 6 months, and 1 year in normal group (P < 0.05). Normal vs. moderate group: CD3 and CD4 cells were higher at 1, 3 and 6 months, and 1 year (P < 0.05), CD8 cells were higher at 1 and 3 months, and 1 year in normal group (P < 0.05). Normal vs. severe group: CD3, CD4 and CD8 cell at 1, 3 and 6 months, and 1 year in normal group (P < 0.05). Mild vs. moderate group: CD3, CD4 and CD8 cells were higher at 1 month in mild group (P < 0.05). Mild vs. severe group: CD4 cells were higher at 1, 3 and 6 month, and 1 year (P < 0.05), CD3 and CD8 cells were higher at 1 month in mild group (P < 0.05). Moderate vs. severe group: CD4 cells were higher at 3 months (P < 0.05), CD8 cells were higher at 6 months in moderate group (P < 0.05). The hepatic T2* values were positively correlated with CD3, CD4 and CD8 cells. The infection rates of Epstein-Barr virus and cytomegalovirus were significantly different among the groups (P < 0.05). Conclusion Iron deposition affects immune recovery of T lymphocytes after allo-HSCT in children with β-thalassemia. The lower the levels of iron deposition, the greater the CD4 cell count.